(3OjhGf GdeYeGQs - (3GdeYeGQ , EHQGgje Hf Ydj Hf EHQGgje,J (B749 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3agPg ofHPI ef fXe GdTjN GdCOjH, hGdNdjY ddHjJ CHj GdXQGFa EHQGgje CUGH bdHj NWGFj HdMXI dTbGFj s
(3BNQgG (B:s
(3ced GdOjhGf HMeO Gddg JYGdi hYhfg, hMSf cQeg hefg s
(3GdfSNI HgG MhGTs
(3ocJHJ GdebOeI Hbde oeNJda hHgGeT GdfSNI JYdjbGJ eJfhYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B60s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B216 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B763s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs